2012
DOI: 10.4028/www.scientific.net/kem.512-515.902
|View full text |Cite
|
Sign up to set email alerts
|

High Frequency Dielectric Properties and Thermal Conductivity of AlN-BN Composites by Spark Plasma Sintering

Abstract: AlN-BN composite is considered to be a promising material for microwave transparent applications. In this paper, a series of AlN-BN composites with various content of BN (0 wt%, 5 wt%, 15 wt% and 30 wt%) were prepared by spark plasma sintering with multiple components sintering additives at a low temperature (1650 °C), and the effect of sintering conditions and composition on the thermal conductivity and high frequency dielectric properties within frequency range from 10 MHz to 1.5 GHz was investigated. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…3(a), the dielectric constant of the composites remains approximately constant up to hundreds of MHz and then decreases sharply. The polarization mechanism within the frequency range from 1 MHz to hundreds of MHz is usually considered to be predominately the relaxation of electronic polarization [8]. We can observe from Fig.…”
mentioning
confidence: 89%
“…3(a), the dielectric constant of the composites remains approximately constant up to hundreds of MHz and then decreases sharply. The polarization mechanism within the frequency range from 1 MHz to hundreds of MHz is usually considered to be predominately the relaxation of electronic polarization [8]. We can observe from Fig.…”
mentioning
confidence: 89%
“…Among the magnetic materials, NiZn ferrite is a soft magnetic material with good magnetic properties [1]. Recently, some researches have demonstrated that adding a certain amount of the magnetic particle to the structural ceramic matrix results in better mechanical and magnetic properties [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%